2005
DOI: 10.1242/jeb.01786
|View full text |Cite
|
Sign up to set email alerts
|

Spatial orientation in echolocating harbour porpoises (Phocoena phocoena)

Abstract: SUMMARY Studies concerning the echolocation behaviour of odontocetes focus mainly on target detection and discrimination, either in stationary animals or in animals approaching a specific target. We present the first data on the use of echolocation for spatial orientation or navigation. Synchronised video and high-frequency recordings were made of two harbour porpoises trained to swim from one position to another across an outdoor pool in order to correlate swimming and echolocation behaviour. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 35 publications
6
62
0
Order By: Relevance
“…The inter-pulse interval depends more on the size of the swimming environment rather than species differences (Akamatsu et al, 1998). This suggests that the tagged harbor porpoise in the present study scanned various distances, while the captive porpoise might only have used its sonar ranging to cover the distance of the enclosure (Verfuss et al, 2005).…”
Section: Article In Pressmentioning
confidence: 85%
See 3 more Smart Citations
“…The inter-pulse interval depends more on the size of the swimming environment rather than species differences (Akamatsu et al, 1998). This suggests that the tagged harbor porpoise in the present study scanned various distances, while the captive porpoise might only have used its sonar ranging to cover the distance of the enclosure (Verfuss et al, 2005).…”
Section: Article In Pressmentioning
confidence: 85%
“…The lag time (signal processing time of an echo in biological sonar) of captive harbor porpoises is 26-36 ms for difficult tasks and 14-19 ms for simpler tasks with individual differences (Verfuss et al, 2005). Here we use a 20 ms lag time for both species to standardise the comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with these morphological changes are other features of their lifestyle, including highly developed auditory abilities such as echolocation. Odontoceti, such as the harbor porpoise (Phocoena phocoena), makes use of echolocation as its primary sensory system when navigating and foraging (Verfub et al, 2005), though it has also been suggested to use its vision while foraging (Teilmann et al, 2007).…”
mentioning
confidence: 99%